2019
DOI: 10.3897/zookeys.846.34372
|View full text |Cite
|
Sign up to set email alerts
|

A new semislug of the genus Laocaia (Gastropoda, Pulmonata, Helicarionidae) from Vietnam

Abstract: A new species of the genus Laocaia Kuzminykh, 1999, Laocaiasimovi Dedov & Schneppat, sp. nov., is described, which was collected from a single locality in northern Vietnam. Color pictures of living specimens are provided. For the first time, information on the ecology and biology of a representative of the genus Laocaia is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
3
3
0
Order By: Relevance
“…2C). This new species has a similar protective behavior to that described by Dedov et al (2019) for Laocaia simovi and Wiktor (2002) for Cryptaustenia saltatoria and Cryptaustenia obesa . If they are touched or caught, they will quickly flip, wag, and twist their foot to escape from the predator (Fig.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…2C). This new species has a similar protective behavior to that described by Dedov et al (2019) for Laocaia simovi and Wiktor (2002) for Cryptaustenia saltatoria and Cryptaustenia obesa . If they are touched or caught, they will quickly flip, wag, and twist their foot to escape from the predator (Fig.…”
Section: Resultssupporting
confidence: 72%
“…Head possesses two pairs of tentacles (=ommatophores in Dedov et al 2019). Lower tentacle is short and same color as head.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, this dancing semislug genus showed an anti-predator behavior by quick dance-like movements or the sudden flipping and wagging tail movement and the fast movement away from the location of threat. This behavior has also been recorded in several helicarionid semislugs: Cryptaustenia species in Papua-New Guinea, Laocaia species in Vietnam, and Muangnua species in Thailand (Wiktor 2002;Dedov et al 2019;Tumpeesuwan and Tumpeesuwan 2019).…”
Section: Discussionsupporting
confidence: 56%
“…Their own anti-predator adaptations, a passive defense by pulling their body into their shell and an active behavior by swinging their shell around, are well documented and are potentially associated with differences in shell traits (Vermeij 1987(Vermeij , 1993Chiba 2007;Baalbergen 2014;Liew and Schilthuizen 2014;Morii et al 2016;Morii and Wakabayashi 2017;Le Ferrand and Morii 2020). In contrast, the evolution of slug and semislug forms have sacrificed the protection offered by possession of a shell for the mobility, fast body movements, and ability to occupy very small spaces afforded by the reduction or elimination of the shell (Solem 1974;Barker 2001;Wiktor 2002;Dedov et al 2019). In our study, this dancing semislug genus showed an anti-predator behavior by quick dance-like movements or the sudden flipping and wagging tail movement and the fast movement away from the location of threat.…”
Section: Discussionmentioning
confidence: 99%
“…The air temperature was approximately 15-20°C, with almost no wind and a cloudy sky. Deroceras laeve was found nowhere else, but several other, indigenous species, including semi-slugs (Helicarionidae), were collected elsewhere on Fansipan Dedov et al (2019), but none together with D. laeve.…”
Section: Methodsmentioning
confidence: 99%